Low vs. high glycemic index carbohydrate gel ingestion during simulated 64-km cycling time trial performance - Earnest, C. P.; Lancaster, S. L.; Rasmussen, C. J.; Kerksick, C. M.; Lucia, A.; Greenwood, M. C.; Almada, A. L.; Cowan, P. A.; Kreider, R. B. (The Journal of Strength and Conditioning Research, 2004)
The effect of low and high glycemic index (GI) carbohydrate (CHO) feedings during a simulated 64-km cycling time trial (TT) has been examined in nine subjects ([mean ± SEM], age = 30 ± 1 years; weight = 77.0 ± 2.6 kg). Each rider completed three randomized, double blind, counter-balanced, crossover rides, where riders ingested 15 g of low GI (honey; GI = 35) and high GI (dextrose; GI = 100) CHO every 16 km. Our results showed no differences between groups for the time to complete the entire TT (honey = 128 minutes, 42 seconds ± 3.6 minutes; dextrose = 128 minutes, 18 seconds ± 3.8 minutes; placebo = 131 minutes, 18 seconds ± 3.9 minutes). However, an analysis of total time alone may not portray an accurate picture of TT performance under CHO-supplemented conditions. For example, when the CHO data were collapsed, the CHO condition (128 minutes, 30 seconds) proved faster than placebo condition (131 minutes, 18 seconds; p < 0.02). Furthermore, examining the percent differences and 95% confidence intervals (CI) shows the two CHO conditions to be generally faster, as the majority of the CI lies in the positive range: placebo vs. dextrose (2.36% [95% CI; -0.69, 4.64]) and honey (1.98% [95% CI; -0.30, 5.02]). Dextrose vs. honey was 0.39% (95% CI; -3.39, 4.15). Within treatment analysis also showed that subjects generated more watts (W) over the last 16 km vs. preceding segments for dextrose (p < 0.002) and honey (p < 0.0004) treatments. When the final 16-km W was expressed as a percentage of pretest maximal W, the dextrose treatment was greater than placebo (p < 0.05). A strong trend was noted for the honey condition (p < 0.06), despite no differences in heart rate (HR) or rate of perceived exertion (RPE). Our results show a trend for improvement in time and wattage over the last 16 km of a 64-km simulated TT regardless of glycemic index.